Complementing Prostate SBRT VMAT With a Two-Beam Non-Coplanar IMRT Class Solution to Enhance Rectum and Bladder Sparing With Minimum Increase in Treatment Time - Sharfo, Abdul Wahab M.; Rossi, Linda; Dirkx, Maarten L. P.; Breedveld, Sebastiaan; Aluwini, Shafak; Heijmen, Ben J. M. (Frontiers in Oncology, 2021)
Purpose Enhance rectum and bladder sparing in prostate SBRT with minimum increase in treatment time by complementing dual-arc coplanar VMAT with a two-beam non-coplanar IMRT class solution (CS). Methods For twenty patients, an optimizer for automated multi-criterial planning with integrated beam angle optimization (BAO) was used to generate dual-arc VMAT plans, supplemented with five non-coplanar IMRT beams with individually optimized orientations (VMAT+5). In all plan generations, reduction of high rectum dose had the highest priority after obtaining adequate PTV coverage. A CS with two most preferred directions in VMAT+5 and largest rectum dose reductions compared to dual-arc VMAT was then selected to define VMAT+CS. VMAT+CS was compared with automatically generated i)dual-arc coplanar VMAT plans (VMAT), ii)VMAT+5 plans, and iii)IMRT plans with 30patient-specific non-coplanar beam orientations (30-NCP). Plans were generated for a 4x9.5Gy fractionation scheme. Differences in PTV doses, healthy tissue sparing, and computation and treatment delivery times were quantified. Results For equal PTV coverage, VMAT+CS, consisting of dual-arc VMAT supplemented with two fixed, non-coplanar IMRT beams with fixed Gantry/Couch angles of 65°/30° and 295°/-30°, significantly reduced OAR doses and the dose bath, compared to dual-arc VMAT. Mean relative differences in rectum Dmean,D1cc, V40GyEq and V60GyEq were 19.4±10.6%, 4.2±2.7%, 34.9±20.3%, and 39.7±23.2%, respectively (all p<0.001). There was no difference in bladder D1cc, while bladder Dmean reduced by 17.9±11.0% (p<0.001). Also, the clinically evaluated urethra D5%,D10%, and D50% showed small, but statistically significant improvements. All patient VX with X=2,5,10,20, and 30Gy were reduced with VMAT+CS, with a maximum relative reduction for V10Gy of 19.0±7.3% (p<0.001). Total delivery times with VMAT+CS only increased by 1.9±0.7min compared to VMAT (9.1±0.7min). The dosimetric quality of VMAT+CS plans was equivalent to VMAT+5, while optimization times were reduced by a factor of 25 due to avoidance of individualized BAO. Compared to VMAT+CS, the 30-NCP plans were only favorable in terms of dose bath, at the cost of much enhanced optimization and delivery times. Conclusions The proposed two-beam non-coplanar class solution to complement coplanar dual-arc VMAT resulted in substantial plan quality improvements for OARs (especially rectum) and reduced irradiated patient volumes with minor increases in treatment delivery times.